Intention to use cryptocurrency: Social and religious perspective - Noorfaiz Athallah Koeswandana; Fakhruddin Amanullah Sugino (Jurnal Ekonomi dan Keuangan Islam, 2023)
Purpose – This study tries to find out what factors influence the intention to use cryptocurrency from a social and religious perspective using Self Determination Theory (SDT) and Theory of Planned Behavior (TPB). Methodology – Respondents were chosen using purposive sampling targeting z generation and analyze using Structural Equation Modeling - Pooled Least Square (SEM-PLS). 100 respondents took part in this study and analyze using SmartPLS 3.2.9 Software. Findings – The result of this study indicates that FoMO and Islamic financial literacy does not have influences on intention to use cryptocurrency while Attitude has a positive effect on intention to use cryptocurrency. The other finding of this study is religiosity and subjective norms has influence on attitude while higher level of religiosity will increase the Islamic financial literacy. Implications – Theoretically, this study contributes to financial behavior and financial technology study. Practically, this study can be used by developer of sharia investment platform to optimize their product. Because even all of our respondents are a moslem, majority of them didn’t investing in sharia product but also don’t have intention to engage in Cryptocurrency. Originality – We believe this study is the first empirical study that investigates the intention to use cryptocurrency from a religious perspective, specifically Islamic financial literacy.